Inefficient Transmissibility of NS-Truncated H3N8 Equine Influenza Virus in Dogs - Song, Manki; Yeom, Minjoo; Park, Nanuri; Kang, Bokyu; Moon, Hyoungjoon; Jeong, Dae-Gwin; Kim, Jeong-Ki; Song, Daesub (Journal of microbiology and biotechnology, 2015)
H3N8 equine influenza virus (EIV) causes respiratory diseases in the horse population, and it has been demonstrated that EIV can transmit into dogs owing to its availability on receptors of canine respiratory epithelial cells. Recently, we isolated H3N8 EIV from an EIV-vaccinated horse that showed symptoms of respiratory disease, and which has a partially truncated nonstructural gene (NS). However, it is not clear that the NS-truncated EIV has an ability to cross the host species barrier from horses to dogs as well. Here, we experimentally infected the NS-truncated H3N8 EIV into dogs, and monitored their clinical signs and viral load in respiratory organs to determine the virus's transmissibility.